2020
DOI: 10.3390/cancers12010207
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific Protease 21 Promotes Colorectal Cancer Metastasis by Acting as a Fra-1 Deubiquitinase

Abstract: Fos-related-antigen-1 (Fra-1), a member of the activator protein-1 (AP-1) transcription factor superfamily, has an essential role in cancer progress and metastasis and Fra-1 is considered a therapeutic target in metastatic cancer including metastatic colorectal cancer (mCRC). However, its regulation at protein level has not yet been clearly elucidated. We found that ubiquitin-specific protease 21 (USP21) increases Fra-1 stability by deubiquitinating Fra-1 and enhances the expression of Fra-1 target genes in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 45 publications
2
32
0
Order By: Relevance
“…In this study, USP21, another member of the USP subfamily of DUBs, was reported to be highly expressed in GC tissue and cells. The expression trend is consistent with that in breast cancer ( Arceci et al, 2019 ) and colorectal cancer ( Yun et al, 2020 ). Previous research found that the nuclear localization of USP21 in pancreas cancer is positively correlated with advanced tumor grades and expression levels, and overexpression of USP21 promotes cell stemness ( Hou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this study, USP21, another member of the USP subfamily of DUBs, was reported to be highly expressed in GC tissue and cells. The expression trend is consistent with that in breast cancer ( Arceci et al, 2019 ) and colorectal cancer ( Yun et al, 2020 ). Previous research found that the nuclear localization of USP21 in pancreas cancer is positively correlated with advanced tumor grades and expression levels, and overexpression of USP21 promotes cell stemness ( Hou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 84%
“…USP21 is proven to deubiquitinate TCF7 ( Hou et al, 2019 ), YY1 ( Xu et al, 2020 ), FOXM1 ( Arceci et al, 2019 ), EZH2 ( Chen et al, 2017 ), RIG-1 ( Fan et al, 2014 ), Fra-1 ( Yun et al, 2020 ), IL-8 ( Peng et al, 2016 ), and other genes to stabilize their expression. This study testified that USP21 in GC cells could bind to GATA3 to regulate its expression.…”
Section: Discussionmentioning
confidence: 99%
“…USP21 ampli cation was also observed in other cancer types (Fig. 4a), which is consistent with previous studies that USP21 regulates cell proliferation and metastasis in colorectal cancer and pancreas cancer (Yun et al 2020;Hou et al 2019). Next, we con rmed the expression levels of PD-L1 and USP21 in LUSC and found that upregulated expression of PD-L1 accounted for 80% (395 of 494) of LUSC samples, while USP21 accounted for 76% (375 of 494) of LUSC samples (Fig.…”
Section: Usp21 Functions As a Pd-l1 Dubsupporting
confidence: 90%
“…Fra-1 is not able to transform the cells on its own. However, a high expression of Fra1 promotes cell proliferation and survival, as well as angiogenesis of human cancers (32)(33)(34). Furthermore, overexpression of Fra1 confers chemo/radioresistance in multiple human cancer models (35,36).…”
Section: Discussionmentioning
confidence: 99%